(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2019)
Introduction: The burden of kidney disease patients requiring renal replacement therapy is increasing day by day. Hemodialysis (HD) constitutes the most common form of renal replacement therapy (RRT) worldwide. Determining the adequacy of hemodialysis, Urea kinetic modeling (UKM) is an important tool for this. The aim of this study was to determine hemodialysis adequacy by UKM. Material & Methods: A total 137 patients were sampled in dialysis center of Combined Military Hospital (CMH) Dhaka. This was a cross sectional study. Data were collected from predialysis, postdialysis and next predialysis blood sample. Mean of adequacy parameters like single pool Kt/V (spKt/V), urea reduction ratio (URR), time average concentration of urea (TACurea) and normalized protein catabolic rate (NPCR) were calculated and compared between twice and thrice per week hemodialysis groups. Also compared adequacy variables between groups who achieved cutoff values and who did not achieve it. Results: One hundred (72.99%) patients were on 8 hours/week and 37 (27%) were on 12 hours/week hemodialysis session. Only 21(21%) and 16(43%) could achieve spKt/V cut off value among 8 hour and 12 hours group respectively. Eighty (58.39%) patients had URR < 65% in this study. Blood flow e+250 ml/ min group had significantly better dialysis adequacy than blood flow <250ml/min group, URR (81.31± 10.21 vs. 54.51 ± 11.52 and p-value <0.001), spKt/V (1.99 ± 0.41 vs. 1.41 ± 0.31 pvalue< 0.001) Thrice weekly hemodialysis group achieved better adequacy than twice weekly group. Conclusion: Frequency and blood flow of dialysis are strongly associated with adequacy of hemodialysis as evidenced by spKt/V and URR value. So to achieve hemodialysis adequacy, increasing the frequency of dialysis from two to three sessions per week is recommended. J Bangladesh Coll Phys Surg 2019; 37(4): 169-174